High hepatitis C virus cure rates with approved interferon‐free direct‐acting antivirals among diverse mainland Chinese patients including genotypes 3a and 3b. Issue 3 (5th August 2020) - Ji, Fanpu; Li, Jie; Liu, Li; Liang, Jing; Wang, Xiaozhong; Liu, Junping; Cai, Dachuan; Huang, Rui; Zhang, Jiajie; Wang, Qi; Nan, Yuemin; Li, Junyi; et al.
Abstract: Background and Aim: Globally, China has the highest chronic hepatitis C (CHC) burden, but its real‐world direct‐acting antiviral (DAA) data are limited. Our aim is to investigate the real‐world outcome of China Food and Drug Administration‐approved DAA therapies across mainland China including those with genotype (GT) 3. Methods: The REAL‐C is a multinational real‐world interferon‐free DAA‐treated CHC registry of several mainland China and other Asian centers. We evaluated the sustained virological response rate 12 weeks after end of treatment (SVR12), adverse events, and treatment effect on liver function and fibrosis (fibrosis‐4 index). Results: We analyzed 859 DAA‐treated CHC patients (6/1/2017–5/30/2019) from 12 mainland China centers (three municipalities and nine provinces): median age 52, 49.9% male, 33.1% cirrhosis, 95% treatment naïve, and 2.5% HBsAg + . The most common GT was GT1b (523, 62.2%), followed by GT2a (156, 18.5%), GT3b (74, 8.8%), GT3a (41, 4.9%), and GT6 (37, 4.4%). SVR12 rates were 98.0% overall (95% confidence interval 96.9–98.8%), 98.1% for GT1b, 96.8% GT2a, 100% GT3a, 97.3% GT3b, and 100% GT6. Baseline cirrhosis and male sex but not prior treatment history, renal dysfunction, age, and GTs were associated with SVR12. For both cirrhotic and non‐cirrhotic patients, there were significant improvement in liver function tests, alpha fetoprotein, and fibrosis‐4 index with SVR12. Serious adverse events were rare (1.1%) with only nine patients discontinuing therapy prematurely and anemia being the most common adverse event (13.1%, mostly with ribavirin). Conclusions: In real‐world Chinese patients with diverse GTs, Chinese Food and Drug Administration‐approved interferon‐free DAAs were well tolerated, provided high cure rates (98.0% overall) including GT3a/3b, and led to improvement of liver function.